PEMANFAATAN VIDEO PEMBELAJARAN BERBASIS DEEP LEARNING UNTUK MENGASAH KEMAMPUAN SPEAKING BAHASA INGGRIS MAHASISWA DALAM DESKRIPSI TERMINOLOGI BIOLOGI TANAMAN - Ni Made Milati (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2026)
his research explores the effectiveness of utilizing video learning, designed with a deep learning approach, to enhance students' English speaking skills, particularly in describing plant biology terminology. In the era of globalization, mastery of academic English and a deep understanding of scientific concepts are crucial, yet students often face challenges in integrating these two aspects. This article outlines how video learning can serve as a strategic medium to facilitate deep learning through detailed visualizations of plant parts (roots, stems, leaves, twigs) and the presentation of models for describing biological terminology in English. This approach is also designed to stimulate speaking practice through student- produced video assignments. The discussion findings indicate that well- structured video learning can improve students' understanding of plant biology terminology and significantly enhance their confidence and fluency in academic English speaking. This integration fosters synergy between scientific content mastery and the development of essential global communication competencies.